The value of supplemental copper and cobalt for steers on fattening rations - Gnadt, K.L.; Smith, E.F.; Richardson, D.; Kramer, J.E.; Dunn, L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Cobalt is one of the more recent minerals discovered to be essential to ruminants. It is necessary for the synthesis of Vitamin B 12 in the rumen. Copper is necessary for hemoglobin formation, along with iron. Corn is considerably lower in copper and cobalt than sorghum grains, according to the National Research Council. Its requirement tables for beef cattle show that 2 to 4 mgs. of copper and .03 to .05 mg. of cobalt are required per pound of feed.
Keywords: Beef; Copper; Cobalt; Steers